Loire Classics: Reviving Classicism in some Loire Poets - Wim Verbaal (Interfaces: A Journal of Medieval European Literatures, 2017)
The term 'Loire poets' has come to refer to a rather undefinable group of poets that in the second half of the eleventh century distinguishes itself through its refined poetics. They are often characterized as medieval humanists thanks to their renewed interest in the classics. Sometimes their movement is labelled a 'classicist' one. But what does this 'classicism' mean? Is it even permitted to speak of medieval 'classicisms'? This contribution approaches the question of whether we can apply this modern label to pre-modern phenomena. Moreover, it explores the changes in attitude towards the classics that sets the Loire poets off from their predecessors and contemporaries. The article focuses on poems by Hildebert of Lavardin, Baudri of Bourgueil, Marbod of Rennes, and Geoffrey of Reims. They are compared with some contemporary poets, such as Reginald of Canterbury and Sigebert of Gembloux.